Unsteady characteristics of S-duct intake flow distortion - Gil-Prieto, Daniel; Zachos, Pavlos K.; MacManus, David G.; McLelland, Grant (Elsevier, 2018)
The unsteady distorted flow fields generated within convoluted intakes can have a detrimental effect on the stability of an aero-engine. The frequency signature in the distorted flow field is of key importance to the engine's response. In this work, time-resolved particle image velocimetry is used to obtain the three-component velocity field at the outlet plane of two S-duct intake configurations for a range of inlet Mach numbers. Proper orthogonal decomposition of the time-resolved velocity data allows the identification of the main frequencies and coherent structures in the flow. The most energetic unsteady structures comprise an in-plane vortex switching mode, associated with a lateral oscillation of the main loss region, and a vertical oscillation of the main loss region. The switching structure occurs at a frequency of St=0.42 and 0.32 for the high and low offset ducts, respectively. The vertical perturbation is associated with a more broadband spectrum between approximately St=0.6–1.0 and St=0.26–1.0 for the high and low offset configurations, respectively. The determined frequencies for these main unsteady flow structures are within the range, which is expected to be detrimental to the operating stability of an aero-engine. The results provide a novel, time-resolved dataset of synchronous velocity measurements of high spatial resolution that enables analysis of the unsteady flows at the exit of complex aero-engine intakes.